INFLUENCE OF PRODUCT QUALITY AND PRICE ON CONSUMER SATISFACTION: A CASE STUDY OF VINTANCAKE - Sa'adah, Khoirunatun; Suyadi , Suyadi (Universitas Terbuka, 2024)
This study aims to determine the influence of product quality and price on consumer satisfaction (Y) in the Vintancake business. The sampling technique used in this study was non-probability sampling, specifically convenience sampling. A total of 50 respondents who had previously purchased Vintancake products were included as the sample for this study. The data analysis was conducted using SPSS version 25. The findings indicate that product quality has a positive and significant effect on consumer satisfaction, with a positive effect of product quality (x1) = 0.199 and a significance value of 0.000 (0.000 < 0.05). Similarly, price also has a positive and significant effect on consumer satisfaction, with a positive effect of price (x2) = 0.294 and a significance value of 0.000 (0.000 < 0.05). Both product quality and price jointly influence consumer satisfaction, with product quality (X1) and price (X2) showing that when both are at 0, consumer satisfaction (Y) increases to 14.892.